أثر دخل الأسرة على تسرب بعض الأبناء من المدارس بمحلية الكاملين ، ولاية الجزيرة ، السودان (2018-2022م) - موسى الرضي, سامية حمد (Gezira Journal of Educational Sciences and Humanities; مجلد 20 عدد 1 (2023), 2026)
هدفت الورقة إلى دراسة العلاقة بين مستوى دخل الأسرة وتسرب بعض الأبناء بمدارس محلية الكاملين، وإلقاء الضوء على أثر ظاهرة تسرب بعض الأبناء من المدارس على دخل الأسرة مستقبلاً بالمحلية. اتبعت الدراسة المنهج الوصفي والتاريخي والإحصائي. جمعت البيانات من المصادر الأولية بجانب المصادر الثانوية، تم أخذ عينة بلغ حجمها الكلي (302) أسرة تمثل (5%) من مجتمع الدراسة، تم تحليل البيانات ببرنامج الحزم الإحصائية للعلوم الاجتماعية (SPSS). توصلت الدراسة إلى عدة نتائج أهمها: هنالك علاقة بين انخفاض مستوى دخل الأسرة وتسرب بعض الأبناء من المدارس بمحلية الكاملين، حيث أثبتت نتائج الدراسة أن ضعف الدخل لا يتوافق مع الارتفاع الكبير في أسعار السلع والمتطلبات الدراسية إذ أن (94.1%) من المبحوثين يتراوح متوسط دخلهم الشهري بين (10-29) ألف جنيه، (75.5%) من حجم العينة لا يغطي دخلهم الشهري احتياجات الأسرة، (94.4%) من عينة الدراسة يتسرب أبناؤهم من المدارس ويشكل منهم (65.6%) من المتسربين تركوا الدراسة بسبب عدم مقدرة الأسرة على توفير المصروفات الدراسية لانخفاض دخلها، و(68.7%) من عينة الدراسة يؤكدون أن  الأبناء الذين تركوا الدراسة يعملون من أجل المساهمة في احتياجات الأسرة المعيشية و(29.5%) منهم أفاد بأنّهم يعملون من أجل تعليم إخوانهم، وللتسرب أثر سلبي على دخل الأسرة مستقبلاً نتيجة تسرب بعض أبنائها من المدارس، وقد أكدت نتائج الدراسة أن (95.5%) من حجم العينة أشاروا لوجود أثر سلبي للتسرب على دخل الأسرة مستقبلاً ، وأفاد (52.6%) منهم أن حجم التأثير سيصل إلى(50%) كحد أقصى. توصي الدراسة بإعلان مجانية التعليم، إدخال الأسر في مشاريع التمويل الأصغر، تعليم الأبناء بالأقساط عبر البنوك، وتكفّل المنظمات الخيرية بتعليم الأبناء . The paper aimed to study the relationship between the level of family income and the school dropout rate among children in Al-Kamleen Locality, and to shed light on the impact of the phenomenon on family income in the future in the locality. The study followed the descriptive, historical and statistical method. The data were collected from both primary and secondary sources. A total sample size of (302) families was taken, representing (5%) of the study population. The data was analyzed using the statistical package of social sciences (SPSS). The study reached several results, the most important points of which are the following: There was a correlation between low family income and student dropout rates in the locality. The study proved that low income levels did not keep pace with the significant rise in the prices of goods and school requirements. The average monthly income of (94.1) of the subjects ranged between (10 – 29) Sudanese pounds. (75.5) of them reported that their monthly income did not cover their family's needs. Furthermore, (94.4%) of them indicated that their children dropped out of school. Among these dropouts, (65.6%) left their studies because the families were unable to afford the school expenses due to low income. Additionally, (68.7%) of the sample confirmed that their children who left school were working to contribute to the family's living requirements, while (29.5%) stated that they worked to support their siblings' education. Dropping out of school would have a negative impact on future household income, as confirmed by (95.5%) of the sample. (52.6%) of the subjects reported that the magnitude of this impact would reach a maximum of (50%). The study recommends providing free education, involving families in microfinance projects, facilitating tuition payments through bank installments, and ensuring that charitable organizations sponsor children's education.